Coupling Ultrasound with Heat-Reflux to Improve the Extraction of Quercetin, Kaempferol, Ginkgetin and Sciadopitysin from Mairei Yew Leaves - Chunjian Zhao (Applied Sciences, 2019)
The coupling of ultrasound and heat⁻reflux extraction (UHRE) was developed for separation for quercetin (QU), kaempferol (KA), ginkgetin (GI) and sciadopitysin (SC) from Mairei Yew leaves. The Box⁻Behnken design was used to optimize the UHRE conditions for obtaining the maximum yield of flavonoids. The optimal extraction conditions were as follows: boiling 80% methanol (V/V) for extraction solvent, 20 min for the extraction time, 200 W for the ultrasonic power and 26 mL/g for the liquid⁻solid ratio. By UHRE, the yields of QU, KA, GI and SC were, respectively, 0.109, 0.406, 0.031 and 0.355 mg/g, and total yield of four flavonoids was 0.901 mg/g, which were, respectively, 1.25-fold and 1.23-fold higher than those by using ultrasonic-assisted extraction (UAE) and heating reflux extraction (HRE). Moreover, the extraction time for the equilibrium yields of flavonoids using UHRE was 83.3% and 27.8%, respectively, less than the corresponding time using UAE and HRE. Compared with HRE and UAE, UHRE showed the increase of cell disruption degree as observed by scanning electron microscopy, which may be the reason for high yield and rapid extraction of target compounds.